Pengaruh Interaksi Remaja dengan Keluarga dan Teman serta Self-Esteem terhadap Perilaku Prososial Remaja Awal - Hotmauli Adina Riska; Diah Krisnatuti; Lilik Noor Yuliati (Jurnal Ilmu Keluarga dan Konsumen, 2018)
Adolescent tend to do the anti-social behavior, so it needs prevention step by developing prosocial behavior. Thisstudy aimed to analyze the effect of characteristic, family interaction, friend interaction and self-esteem onprosocial behavior among early adolescents. This research was a cross-sectional study. The location of theresearch was conducted in Junior High School X in Bogor District which was chosen purposively. The examplesof this study were 200 adolescents with same sex siblings (100 girls and 100 boys) which was chosen by clusterrandom sampling technique. The results showed that there was no significant difference in interaction with thefather between girls and boys. Closeness dimension of girl’s interaction with mother and girl’s interaction with afriend were higher than boy’s. Closeness and discord dimensions of girl’s interactions with same-sex siblingswere higher than boy’s. Self-esteem didn’t have a significant difference between girls and boys, but girls weremore prosocial than boys. Closeness dimension of interaction with mother, interaction with the sibling, andinteraction with a friend also self-esteem can improve prosocial behavior, but interaction with father didn’tsignificantly influence to prosocial behavior.